Asymptotics and stabilization for dynamic models of nonlinear beams - Araruna, Fagner D.; Braz E Silva, Pablo; Zuazua, Enrique (Proceedings of the Estonian Academy of Sciences, 2010)
We prove that the von Karman model for vibrating beams can be obtained as a singular limit of a modified Mindlin-Timoshenko system when the modulus of elasticity in shear k tends to infinity, provided a regularizing term through a fourth-order dispersive operator is added. We also show that the energy of solutions for this modified Mindlin-Timoshenko system decays exponentially, uniformly with respect to the parameter k, when suitable damping terms are added. As k -> infinity one deduces the uniform exponential decay of the energy of the von Karman model.
CRIS-Team WoS Importer:2019-12-13